Climate change – health impacts due to changes in the indoor environment; research need - Crump, Derrick (Cranfield University, 2012)
People in industrialised countries spend approximately 80% of their time indoors and the young and the elderly and people in poor health are likely to spend considerably more time indoors, particularly at home. Therefore all aspects of health that are related to environmental conditions can be impacted by the quality of the indoor environment. The indoor environment should provide shelter from the extremes of the outdoors and maintain a comfortable indoor climate, particularly thermal comfort, and provide appropriate protection against other environmental factors including pollutants, infectious agents and noise. Expected future changes in climate resulting from the impact of man on the atmosphere leading to global warming will impact the effectiveness of buildings to provide appropriate shelter and associated environmental conditions.